Could the Madagascar bloom be fertilized by Madagascan iron?. Issue 8 (21st August 2015) - Srokosz, M. A.; Robinson, J.; McGrain, H.; Popova, E. E.; Yool, A.
Abstract In the oligotrophic waters to the east of Madagascar, a large phytoplankton bloom is found to occur in late austral summer. This bloom is composed of nitrogen fixers and can cover up to ∼1% of the world's ocean surface area. Satellite observations show that its spatial structure is closely tied to the underlying mesoscale eddy field in the region. The causes of the bloom and its temporal behavior (timing of its initiation and termination) and spatial variability are poorly understood, in part due to a lack of in situ observations. Here an eddy resolving 1/12° resolution ocean general circulation model and Lagrangian particle tracking are used to examine the hypothesis that iron from sediments around Madagascar could be advected east by the mesoscale eddy field to fertilize the bloom, and that variability in advection could explain the significant interannual variability in the spatial extent of the bloom. The model results suggest that this is indeed possible and furthermore imply that the bloom could be triggered by warming of the mixed layer, leading to optimal conditions for nitrogen fixers to grow, while its termination could be due to iron exhaustion. It is found that advection of Madagascan iron could resupply the bloom region with this micronutrient in the period between the termination of one bloom and the initiation of the next in the following year.